Twisting the ethano-Tröger's base: the bisamide - Pereira, R; Pfeifer, L; Fournier, J; Gouverneur, V; Cvengroš, J (Royal Society of Chemistry, 2016)
The typically planar amide when incorporated into bicyclic systems can undergo a significant distortion from planarity resulting in physical properties and reactivity that deviate from classical amide behaviour. Herein, we report a succinct protocol that utilises potassium permanganate to selectively α-oxygenate the benzylic position of ethano-Tröger's base derivatives to yield a new class of twisted bisamides. Additionally, we report the first synthesis of an ethano-Tröger's base derivative bearing substituents in the positions ortho to the nitrogen atoms.